2021
DOI: 10.21037/atm-21-3641
|View full text |Cite
|
Sign up to set email alerts
|

Key immune-related gene ITGB2 as a prognostic signature for acute myeloid leukemia

Abstract: Background: The tumor microenvironment (TME) has an essential role in tumorigenesis, progression, and therapeutic response in many cancers. Currently, the role of TME in acute myeloid leukemia (AML) is unclear.This study investigated the correlation between immune-related genes and prognosis in AML patients.Methods: Transcriptome RNA-Seq data for 151 AML samples were downloaded from TCGA database (https://portal.gdc.cancer.gov/), and the immune related genes (irgs) were selected from Immport database.Bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Breast tumors consist of cancerous and non-cancerous cells, which have rarely been studied; moreover, enriched pathways were found to be related to the tumor microenvironment. Therefore, we identified the composition of immune cells in breast tumors, and investigated the correlation between the key genes and infiltrating immune cells in breast cancer patients [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breast tumors consist of cancerous and non-cancerous cells, which have rarely been studied; moreover, enriched pathways were found to be related to the tumor microenvironment. Therefore, we identified the composition of immune cells in breast tumors, and investigated the correlation between the key genes and infiltrating immune cells in breast cancer patients [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found the co-association with four genes between the Romboutsia genus and Ruminococcus gnavus at the strict threshold ( p < 5 × 10 –4 ). It is reported that ITGB2 had a powerful influence on immune cell infiltration into the acute myeloid leukemia (AML) tumor microenvironment ( Wei et al, 2021 ). OTULIN , coding the M1-specific deubiquitinase, is essential for preventing TNF-associated systemic inflammation in humans and mice and critical for restraining life-threatening spontaneous inflammation and maintaining immune homeostasis ( Damgaard et al, 2016 ; Hoste et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ITGB2 was proved to promote the effects of the migration capability and invasion capability of breast cancer via biological function experiments [ 30 ]. ITGB2 was identified to be the key immune-related gene in acute myeloid leukemia patients, while the high expression of ITGB2 was related to the poor prognosis of acute myeloid leukemia patients [ 31 ]. These results indicated that ITGB2 plays significant roles in tumorigenesis and progression.…”
Section: Discussionmentioning
confidence: 99%